Community prevalence of SARS-CoV-2 in England during April to November 2020: Results from the ONS Coronavirus Infection Survey - Pouwels, K; House, T; Pritchard, E; Robotham, JV; Birrell, PJ; Gelman, A; Vihta, K-D; Bowers, N; Boreham, I; Thomas, H; Lewis, J; Bell, I; et al. (Elsevier, 2020)
Background Decisions about the continued need for control measures to contain the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) rely on accurate and up-to-date information about the number of people testing positive for SARS-CoV-2 and risk factors for testing positive. Existing surveillance systems are generally not based on population samples and are not longitudinal in design.